Indonesian and Thai EFL Learners’ Extensive Listening through Podcasts: A Self-Directed English Learning - Andini, Intan Ambaria; Burhanuddin, Ahmad (Universitas Negeri Semarang, 2022)
When language learners regulate self-improvement activities in their spare time, a broader space for exploration emerges. The purpose of this paper is to present a narrative study of two young adult EFL learners from Indonesia and Thailand who routinely schedule extensive listening through podcasts for their self-directed English learning. Data for this study were gathered through the use of learners' learning diaries and interviews. They were also subjected to thematic analysis. The researcher claims that this study will provide empirical insights into the lived experiences of independent English learners while also clarifying that learning outside of the classroom is no less meaningful or beneficial than learning in the classroom. Some of the factors that motivated learners to engage in this learning practice were the variety, multitasking, and flexibility of podcasts, as well as personal preferences for auditory learning, opportunities to learn other things besides English, and an unwavering future goal toward study and work advancement. Vocabulary enrichment, speech pace and accent recognition, fluency and pronunciation improvement, as well as a stronger knowledge of pragmatic skill and natural dialogues were highlighted as six major areas of their practice that had an influence.